Analisis produksi optimum pada industri keripik singkong (studi kasus pada industri keripik singkong Rajawali di desa Rundeng kecamatan Johan Pahlawan kabupaten Aceh Barat) - . Agustiar (Jurnal Ilmu Pertanian Indonesia, 2011)
This study aims to determine the optimum production from each of the factors of of cassava industry, andlabor in Rajawali cassava chips industry, as well as research methods using case studies. Cassava Chips industries located in Johan Pahlawan subdistrict, West Aceh. The magnitude of the factors of production on cassava chips were analyzed with Cobb Douglas equation, demonstrating the value keofisien (r2) was 0.963, 0.613 for X1, 0,035 for X2 of and 0,0223 for X3 of and Fcalculated = 67.734, F table = 4.07. Its means that the factors of meterial (cassava) as X1, cooking oil as X2 and labor as X3 can explain the cassava chips for 99.73°/o, while 0.27% again explained by other factors beyond the models.